Does the Indonesian National Army develop democracy and human rights? a comparative perspective - Anwar, Anwar; Salmah, Halimatus Khalidawati; Fatkhurohman, Fatkhurohman (Legality : Jurnal Ilmiah Hukum, 2024)
This study analyses the role of the TNI in the development of rule-of-law democracy and human rights. The study compares the approaches and challenges of strengthening democracy through military means with those of the US. Some of the questions addressed include the role of the TNI in the development of constitutional democracy and human rights in Indonesia and the comparative role of the TNI and the U.S. Armed Forces in supporting the principles of democracy and human rights. This research uses a comparative approach by comparing legal literature and case studies from Indonesia and the United States. This research shows that the TNI has an important role in building a democracy based on law and human rights in Indonesia. The United States military and the TNI have several key aspects to illustrate their respective strengths and challenges for comparison. First, regarding civilian control and political influence, the US Armed Forces have a more established system of civilian control and political separation than the TNI. Nevertheless, the TNI has shown significant progress in reducing its political influence and strengthening civilian control. Second, in human rights education and training, the US Armed Forces generally have a more structured and tested system of human rights training and supervision compared to the TNI, which is still in the process of strengthening. Third, in oversight and accountability, the US Armed Forces generally have more structured and effective oversight and accountability mechanisms than the TNI. However, significant efforts have been made in Indonesia to improve these systems. Both countries have their strengths and weaknesses, but it is important to recognize the achievements and efforts of both.